'And we gossip about my life as if I am not there': An autoethnography on recovery from infidelity and silence in the academic workplace. (November 2022) - van de Berg (pseudonym), Truus
In this autoethnography, I engage with betrayal trauma from my husband's infidelity as it relates to recovery and my academic identity, and my work performance. As I navigate between the trauma, the stigma and taboo, the shame and lack of knowledge, my responsibilized academic self, the collegial interactions, and the question of whether keeping silent robbed me of my voice, I distinguish toxic secrets, hurtful silencing and healing silence . Although the exploitative nature of the academic workplace had never been more visceral, I also found that a tending silence contributed to my protection and my recovery. In silence, my academic life is opening up to embracing needs rather than enduring hardships, to inviting rather than striving, to vulnerability rather than empowerment.